2021
DOI: 10.3390/horticulturae7110510
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Drought Damages by Exogenous Chitosan and Yeast Extract with Modulating the Photosynthetic Pigments, Antioxidant Defense System and Improving the Productivity of Garlic Plants

Abstract: Garlic is an important vegetable in terms of its economic value and also as a medicinal plant. In this study, chitosan (300 mM) and yeast extract (8 g/L) were used individually or in combination to improve the yields of garlic plants under drought conditions (i.e., 75% and 50% of the water they would normally receive from irrigation) for two seasons. Significant decreases in numbers of leaves per plant and plant height, plant dry weight, relative water content, and chlorophyll a and b concentrations were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 65 publications
3
38
0
Order By: Relevance
“…Climate change represents a major challenge in the future that will intensively reduce crop yield [ 23 ] and the quality of staple grains [ 24 ]. Temperature flocculation during grain filling greatly affects the accumulation of protein in the developing wheat kernel and, consequently, alters the functional properties of the resulting flour, including dough properties and baking quality [ 13 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Climate change represents a major challenge in the future that will intensively reduce crop yield [ 23 ] and the quality of staple grains [ 24 ]. Temperature flocculation during grain filling greatly affects the accumulation of protein in the developing wheat kernel and, consequently, alters the functional properties of the resulting flour, including dough properties and baking quality [ 13 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was determined that the RWC parameter (Figure 1) increased at the S3 dose, where the salt stress was the highest, especially in the Ch2 application. Abdelaal et al (2021) reported that the RWC increased by 36.8% in the study they applied chitosan and yeast extract to the garlic plant under water stress conditions. Mazrou et al (2021) reported that in a 2 year study in which they applied chitosan nanoparticles to Matricaria chamomilla plant, they provided an increase in RWC compared to the control, and they achieved the maximum value especially in the application of 300 mg L -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Drought is a widely recognized factor that affects plant growth [ 10 , 39 ]. Plants subjected to drought typically reflect a lower production of biomass as the water reduction from soil to the plant decreases cell division and eventually is reflected in less biomass production, including the roots [ 8 ]. Some plant species allocate more biomass to the roots trying to acquire resources as a survival strategy, but when the plant species are subject to both drought and competition, this strategy might not be sufficient [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…These annual species fiercely compete for water and nutrients with the perennial vegetation, especially at the seedling stage, quickly replacing the perennial cover with monocultures that eventually function as fuels for fire that further enhance their dominance [ 5 , 6 ]. Another challenge for plant species establishment is drought, which is a driver of successional processes in semi-arid systems and a barrier to the reestablishment of sagebrush species post-disturbance [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%